The taxonomic identity of the neglected Racomitrium stenocladum (Bryophyta, Grimmiaceae) - Larraín, Juan (2011)
The genus Bucklandiella Roiv. (sensu Ochyra et al. 2003), one of four segregates of Racomitrium Brid., is the most diverse group of the Racomitrioideae in southern South America, with 12 species. Most taxa in the area belonging to Bucklandiella have been moved from Racomitrium by Ochyra et al. (2003), but Racomitrium stenocladum Dusén, treated by Deguchi (1984) as a synonym of B. orthotrichacea (Müll.Hal.) Bednarek-Ochyra & Ochyra has not. In our opinion it represents a distinct taxon, and is here transferred into Bucklandiella.